2021
DOI: 10.31557/apjcp.2021.22.3.935
|View full text |Cite
|
Sign up to set email alerts
|

The Apoptotic Effect of Trichinella spiralis Infection Against Experimentally Induced Hepatocellular Carcinoma

Abstract: Background: Hepatocellular carcinoma (HCC) is the sixth most common type of cancer. Prognosis of HCC remains unsatisfactory. Therefore, developing new therapeutic modalities is still mandatory. Tumor biotherapy is a novel concept developed as a therapeutic strategy for cancer treatment. There is a similarity between the regulatory mechanism of Trichinella spiralis nurse cell formation and tumor cell apoptosis signal regulation. Objectives: Induction of apoptosis by T. spiralis can represent a new strategy for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“… Elhasawy et al (2021) showed that T. spiralis infection in hepatocellular carcinoma (HCC) animal model produced a certain level of decreased progression of the tumor with increased rate of apoptosis as shown by the decreased expression of Bcl-2 at 30- and 40-days post-infection and subsequently had a positive impact on the survival of rats. Other studies involving the anti-tumor effect of Trichinella infection in different tumor models are reviewed by Liao et al (2018) .…”
Section: Trichinella -Derived Molecules: a Panacea For Moder...mentioning
confidence: 99%
“… Elhasawy et al (2021) showed that T. spiralis infection in hepatocellular carcinoma (HCC) animal model produced a certain level of decreased progression of the tumor with increased rate of apoptosis as shown by the decreased expression of Bcl-2 at 30- and 40-days post-infection and subsequently had a positive impact on the survival of rats. Other studies involving the anti-tumor effect of Trichinella infection in different tumor models are reviewed by Liao et al (2018) .…”
Section: Trichinella -Derived Molecules: a Panacea For Moder...mentioning
confidence: 99%
“…Due to the high mortality rate and high risk of recurrence after treatment, new treatment methods are mandatory (Ringelhan et al, 2018;McGlynn et al, 2021). The regulatory mechanism of T. spiralis nurse cell formation is similar to tumor cell apoptosis signal regulation (Elhasawy et al, 2021). Trichinella spiralis nurse cell formation is a complex process and involves differentiation and cell cycle arrest of infected muscle cells.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…The first group is the negative control group, which was left untreated. For the other three groups, carbon tetra chloride was employed at a dose of 1 ml/kg twice a week for three months to develop HCC [5]. Rats in the positive control group received no further treatment and in the palm date group received 400 mg/kg body weight per day of date fruit extract [6].…”
Section: Experimental Designmentioning
confidence: 99%